Effects of phospholipase C inhibition on the regulation of membrane lipid metabolism in maize leaves - Wei, Yulei; Cai, Zhicheng; Che, Zhiyuan; Guo, Xu; Ge, Shengnan; Che, Xinyang; Deng, Jie; Zhang, Haiyang; He, Lin; Xu, Jingyu (Frontiers in Plant Science, 2025)
IntroductionPhospholipase C (PLC) is an enzyme that catalyzes the hydrolysis of glycerophospholipids and can be classified as phospholipase-specific PLC (PI-PLC) and non-specific PLC (NPC) depending on its specific substrate.MethodsIn this study, neomycin sulfate (NS, 100 mM) was used to inhibit the activity of phospholipase C in maize seedlings, and the effect of phospholipase C on lipid metabolism was investigated by combined analysis of transcriptome and lipidome.ResultsLipidomic analysis showed that when PLC was inhibited, the content of phospholipids showed more than 10% increase due to the elevated accumulation of PC and PE. At the same time, transcriptomic data suggested an activation of the de novo biosynthesis of PC and PE from choline and ethanolamine via upregulated CCT and PECT, respectively. Thus, the inhibition of phospholipid hydrolysis and the enhancement of de novo synthesis together contribute to the increase in the total phospholipids. Glycolipids account for around 60% of the total lipids in leaves. Under NS treatment, MGDG decreased significantly, while DGDG increased.DiscussionOur results indicate that NS treatment may cause damage to photosynthetic membrane lipids, whereas the increase in bilayer lipid DGDG may provide a kind of protection to maintain the stability of chloroplasts. These findings suggest that phospholipase C plays a key role in plasma membrane metabolism.